Analisis Faktor Penyebab Orientasi Seksual Menyimpang Pada Narapidana Perempuan Di Lapas Klas II A Pekanbaru - Indrid Weddy Viva Febrya; Elmirawati Elmirawati (UIR PRESS, 2017)
The purpose of this study was to analyze: (1) the lesbian behavior description inwoman’s prison, (2) deviant sexual orientation causing factors of female prisoners, and(3) appropriate treatment for lesbian behavior in women's prisons. This study wasconducted in woman’s prison clas IIA, located on the Bindanak street no.1 Pekanbaru.The research was conducted in March 2018. The research using qualitative method andelaborated by descriptive analythic way. The subjects of the study were 12 femaleprisoners selected by purposive sampling with the following characteristics: 1.Appearance that was not gender appropriate, 2. Recognizing that having a deviantsexual orientation, 3. recommendation by the officer of prison. Data processing is doneby analyzing the result of observation and interview. The result of this research isconcluded that 1) lesbian description in Female prison Class IIA Pekanbaru is a femalewho feel herself as good man by physically and psychic. Sexual intercourse is describedas two women who are attracted to each other, doing relationships like lovers. 3 peoplestill have an interested with a man, while the other 9 people are not at all. Physicalappearance of 11 subjects like as a man, the hair crop, wearing T-shirts, trousers andwear a jacket, their body language is also made dashing, While 1 person usedheadscarf and still seen as female, 2) The causing factors of lesbian behavior are 3people because of environmental factor and 9 others have felt the disorder of sexualorientation since adolescence, where the abnormality is felt happened naturally and 3)treatment appropriate for lesbian in woman’s prison are to provide informationservices and socialization of LGBT impact on physical and psychological health,providing guidance and counseling services of individuals and groups, religiousguidance and counseling services as well as religious lectures provided by experts.